2019
DOI: 10.3390/vaccines7040216
|View full text |Cite
|
Sign up to set email alerts
|

Polyamine Transport Protein PotD Protects Mice against Haemophilus parasuis and Elevates the Secretion of Pro-Inflammatory Cytokines of Macrophage via JNK–MAPK and NF–κB Signal Pathways through TLR4

Abstract: The potD gene, belonging to the well-conserved ABC (ATP-binding cassette) transport system potABCD, encodes the bacterial substrate-binding subunit of the polyamine transport system. In this study, we found PotD in Haemophilus (Glaesserella) parasuis could actively stimulate both humoral immune and cellular immune responses and elevate lymphocyte proliferation, thus eliciting a Th1-type immune response in a murine immunity and infection model. Stimulation of Raw 264.7 macrophages with PotD validated that Toll-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 56 publications
1
13
1
Order By: Relevance
“…In previous studies, we and others have found that PotD is a stress-responsive protein and one of the differentially expressed virulence-related proteins in G. parasuis [Han et al, 2007;Zhang et al, 2014a]. We also found that recombinant PotD protein in G. parasuis could trigger an effectively immunoprotective effect against severe pathological lesions in a mouse model by triggering both cellular and humoral immunity [Dai et al, 2019b]. However, little evidence of the exact biological function of PotD, especially whether it is related to bacterial virulence in vivo, was unveiled in G. parasuis.…”
Section: Introductionsupporting
confidence: 51%
See 3 more Smart Citations
“…In previous studies, we and others have found that PotD is a stress-responsive protein and one of the differentially expressed virulence-related proteins in G. parasuis [Han et al, 2007;Zhang et al, 2014a]. We also found that recombinant PotD protein in G. parasuis could trigger an effectively immunoprotective effect against severe pathological lesions in a mouse model by triggering both cellular and humoral immunity [Dai et al, 2019b]. However, little evidence of the exact biological function of PotD, especially whether it is related to bacterial virulence in vivo, was unveiled in G. parasuis.…”
Section: Introductionsupporting
confidence: 51%
“…The anti-rPotD antisera were prepared as previously described [Dai et al, 2019b]. Each mouse was immunized subcutaneously on days 0, 14, and 21 with 0.1 mg of rPotD (0.2 ml) containing a one-tenth volume of water adjuvant MONTANIDE™ GEL 01 (SEPPIC, Paris, France) [Xu et al, 2019].…”
Section: Expression/purification Of Recombinant Potd Protein and Preparation Of Mouse Antiserummentioning
confidence: 99%
See 2 more Smart Citations
“…The expression levels of IL-10 and TNF-α in the spleen were upregulated after colostrum-deprived pigs were infected with G. parasuis [ 35 ]. Stimulation of Raw 264.7 macrophages with G. parasuis PotD could induce the production of IL1β, IL6, and TNF-α [ 36 ]. Therefore, these cytokines play important roles in the inflammatory damage caused by G. parasuis infection.…”
Section: Discussionmentioning
confidence: 99%